Implementasi Discovery Learning untuk Mengetahui Hasil Belajar Kognitif Mata Pelajaran IPAS di SMKN Mojoagung - Fatikhatun Nikmatus Sholihah (Universitas Nusantara PGRI Kediri, 2024)
The discovery learning learning model is a learning model that can develop or improve student learning outcomes in the cognitive domain. This research aims to determine the influence of the implementation of the discovery learning learning model on cognitive learning outcomes in IPAS lessons at SMKN Mojoagung. This research is quantitative research using a quasi experimental design model. The research used a one group pretest-posttest design method, starting with a pre-test (initial test). After that, it was followed by a post-test (final test). The subjects of this research were class X RPL (Software Engineering) students, totaling 33 students. The data collection technique uses a question giving test (pretest dan postes). Quantitative descriptive analysis technique. The research results showed that students' cognitive learning outcomes increased from 69.46 to 88.72. Based on the results of the t test, sign <0.05 is obtained, namely 0.000. So it can be concluded that the discovery learning learning model influences cognitive learning outcomes in IPAS lessons at SMKN Mojoagung